The interactive feedback mechanisms between terrestrial water storage and vegetation in the Tibetan Plateau - Deng, Haijun; Chen, Yaning; Chen, Xingwei; Li, Yang; Ren, Zhiguo; Zhang, Zhiwei; Zheng, Zhouyao; Hong, Sheng (Frontiers in Earth Science, 2022)
A component of terrestrial water storage, vegetation is also an influential driver of changes in terrestrial water storage. In the context of warming on the Tibetan Plateau, it is essential to explore the relationship between changes in terrestrial water storage and vegetation in this region to understand further the role of vegetation in the changes of water systems in alpine mountains, for which there is a lack of current research. Our study combines terrestrial water storage anomalies data and vegetation indices to determine how their interact. The results indicate a warming rate of 0.44 °C/decade (p<0.01) over the Tibetan Plateau from 1980-2020, while evapotranspiration trended upward (12.9 mm/decade, p<0.01), which is slower than precipitation (15 mm/decade, p<0.01). On the Tibetan Plateau, spatial-temporal differences in temperature, precipitation, and evapotranspiration dominate the variations in terrestrial water storage. From 2003 to 2011, terrestrial water storage changes were relatively stable, but from 2012 to 2016, they declined. In endorheic basins, terrestrial water storage increased, while in exorheic basins, it decreased. An analysis of partial correlations indicates a negative correlation between the terrestrial water storage anomaly and the temperature. It is found that terrestrial water storage and net precipitation in the Yangtze River Basin and the northeast of the endorheic basins are positively correlated. However, the Qaidam Basin and Yellow River Basin are negatively correlated. Under the current climate change state (the increased rate of precipitation is faster than actual evapotranspiration), vegetation change has an insignificant impact on the changes in terrestrial water storage. In contrast, changes in terrestrial water storage (surplus/deficit) significantly affect vegetation changes (greening/browning) in parts of the Tibetan Plateau. The study's results contribute to a deeper understanding of the relationship between water system changes and vegetation on the Tibetan Plateau.